Flow structure and aerodynamic behavior evolution during train entering tunnel with entrance in crosswind. Issue 175 (April 2018) - Yang, Weichao; Deng, E.; Lei, Mingfeng; Zhang, Pingping; Yin, Rongshen
Abstract: Transient variations in aerodynamic loads are one of the most vital causes of train overturning or derailment. Different infrastructure scenarios display the diversity of corresponding flow structures and aerodynamic load acting to vehicles. Entering a tunnel from crosswind condition is the most common aerodynamic environment of train operation. In this process, a sudden changes of the aerodynamic load on vehicle could increase the risk of derailment and overturning. Using a three-dimensional unsteady compressible flow, the transient variations of flows and pressures structure as a train enters a tunnel with the entrance in crosswind condition is studied. Furthermore, the correlations between the behavior and the temporal evolution of both the aerodynamic coefficients and their change rates have been discussed qualitatively based on lateral force, lift force, overturning moment, yawing moment, and pitching moment. Results showed that transient variations of the flows and pressure structure occurs in both horizontal and vertical direction, and their demarcation line just keeps in stationary at the tunnel entrance, as train moves into tunnel gradually. Because of crosswind located at tunnel entrance, the train's swing movement is manifested as a complex behavior including pulse oscillation, hunting movement and pitching behaviors etc. Besides the aerodynamic coefficients, the change rate of aerodynamic coefficients also seems to be a referential index of hazard assessment of running train for their synchronization. The safety factor of the leading carriage may be an important indicator of the safety assessment of the train during running from an open air in crosswind into a tunnel. Highlights: Transient variations of aerodynamic loads during train entering tunnel from open air under crosswind was studied. Aerodynamic behavior evolution and correlations with aerodynamic loads are discussed. Change rate of aerodynamic coefficients is found in safety assessment of running vehicle.